AGENDA CONTROL AND RECIPROCITY IN SEQUENTIAL VOTING DECISIONS - Urs Fischbacher; Simeon Schudy (Economic Inquiry, 2020)
We study how reciprocity affects the extent to which a chair can exploit her control over an agenda if a committee votes sequentially on a known series of binary proposals. We show in a parsimonious laboratory experiment that committee members form vote trading coalitions favoring early proposals not only when the sequence of proposals is exogenously given, but also when a chair controls the sequence of proposals. Vote trading occurs even though chairs manipulate the agenda in their favor. Punishment for chairs exploiting agenda control is weak as chairs reciprocate support by others more frequently than nonchairs. (JEL C92, D71, D72)
Keywords: 330